Race and the Land in South Africa: African Challenges to Land Policy and Segregation Between 1905 and 1936. - Feinberg, Harvey M. (1999)
Keywords: dept.his; faculty_collection; sabbatical_report

[Biography of Connecticut Governor Ella T. Grasso] - Purmont, Jon E. (Fall;History., 1999)
Keywords: dept.his; faculty_collection; sabbatical_report

Seeds of Empire: The American Revolutionary Conquest of the Iroquois - Mintz, Max M. (University, 1999)
"The American Revolution was a struggle not only for independence, but for the lands of Native Americans. The jewel in this conflict was the upstate New York domain of the Iroquois Six Nations, where fertile river valleys were a magnet for farmers weary of New England's stubborn soil." "While at first intentionally neutral, the Iroquois were soon forced to choose sides between either rebel or British forces. Seeds of Empire recreates the events surrounding General John Sullivan's scorched-earth campaign against the Six Nations of the American Indians of New York and the Eastern territories in 1779, following the surrender of General John Burgoyne's entire British army at the Battle of Saratoga. Abandoned by both the rebels and the British at the end of the revolution and devastated by the ravages of war, the Iroquois found themselves powerless to resist the post-Revolutionary takeover and peopling of their heartland by the new American nation."–Jacket.
Keywords: Sullivan's Indian Campaign; 1779; dept.his; faculty_collection

Francis Kernan: The Life and Times of a 19th Century, Citizen-Politician of Upstate New York - Kernan, Karen Clemens; Kernan, John Devereux; Forbes, Robert P. (Oneida County Historical Society, 1999)
Keywords: dept.his

A social history of wet nursing in America: From breast to bottle. - Metaxas, VA (Isis, 1999)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000085890500069
Keywords: dept.his

Ghaylan Al-Dimashqi: The isolation of a heretic in Islamic historiography - Judd, SC (International Journal of Middle East Studies, 1999)
7 citations (Crossref) [2023-10-31] tex.organization: Middle E Studies Assoc tex.unique-id: ISI:000080330000002 29th Annual Meeting of the Middle-East-Studies-Association, WASHINGTON, D.C., DEC 06-10, 1995
Keywords: dept.his

Book Review: War and the illiberal conscience: coker, christopher: boulder: westview press 240 pp., publication date: april 1998 - Paddock, Troy (History: Reviews of New Books, 1999)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/076-456-415-896-519 tex.type: [object Object]
Keywords: book.review; dept.his